Role of Oral Rifampicin in Chronic Central Serous Chorioretinopathy - , Nasir Memon, A. Sami Memon, P.S. Mahar (Pakistan Journal of Ophthalmology, 2021)
Purpose: To determine the improvement in visual acuity and central macular thickness in patients with chronic central serous chorioretinopathy (CSCR) with oral Rifampicin. Study Design: Quasi experimental study. Place and Duration of Study: Isra Postgraduate Institute of Ophthalmology, Al-Ibrahim Eye Hospital, Karachi. From September 2015 to December 2016. Material & Methods: Ten eyes of 10 patients having chronic CSCR of more than 6 months duration were prospectively treated with oral Rifampicin 450 mg in single oral dose for 3 months duration. All patients were followed-up for 12 months. Results: Ten eyes of 10 patients were included in the study. The gender distribution showed 8 male (80%) and 2 female (20%) patients. There were five right and five left eyes. Mean age of our patients was 40.10 ? 5.1 years (Range 34 ? 46 years). Mean duration of patient?s ocular symptoms was 9.4 ? 2.9 months with range of 6 ? 14 months. Patient?s visual acuity improved at 3 months follow-up. Mean Pre-treatment central macular thickness was 350 ? 82.3 ?m improving to 232 ? 54.3 ?m at 3 months treatment. Conclusion: All patients with chronic CSCR of more than 6 months duration showed improvement in their vision and central macular thickness with oral Rifampicin taken for 3 months. Key Words: Rifampicin, Central serous chorioretinopathy, Visual acuity, Central macular thickness.